Implementing eccentric resistance Training - Part 1: A brief review of existing methods - Suchomel, T. J.; Wagle, J. P.; Douglas, J.; Taber, C. B.; Harden, M.; Haff, G. G.; Stone, M. H. (Journal of Functional Morphology and Kinesiology, 2019)
The purpose of this review was to provide a physiological rationale for the use of eccentric resistance training and to provide an overview of the most commonly prescribed eccentric training methods. Based on the existing literature, there is a strong physiological rationale for the incorporation of eccentric training into a training program for an individual seeking to maximize muscle size, strength, and power. Specific adaptations may include an increase in muscle cross-sectional area, force output, and fiber shortening velocities, all of which have the potential to benefit power production characteristics. Tempo eccentric training, flywheel inertial training, accentuated eccentric loading, and plyometric training are commonly implemented in applied contexts. These methods tend to involve different force absorption characteristics and thus, overload the muscle or musculotendinous unit in different ways during lengthening actions. For this reason, they may produce different magnitudes of improvement in hypertrophy, strength, and power. The constraints to which they are implemented can have a marked effect on the characteristics of force absorption and therefore, could affect the nature of the adaptive response. However, the versatility of the constraints when prescribing these methods mean that they can be effectively implemented to induce these adaptations within a variety of populations.